La contaminación ambiental que causan los turistas a la cascada la chorrera del recinto el triunfo del cantón caluma provincia de Bolívar - Larrea Cevallos, Íngrid Sofía (2016)
The research that has been carried out with the purpose of analyzing why the environmental contamination in the waterfall the Chorrera of the precinct the triumph Canton Caluma and to be part of the possible solutions in the management of the wastes executing a field investigation by means of surveys and with The results obtained will be possible to consider possible solutions to improve the case. The lack of culture of the human being in his bad practice at a given time in the face of contemporary society and its form of production and consumerism has negatively influenced the conservation of its sustainable environment. Through the proposals of training workshops and the placement of garbage cans will serve to avoid environmental pollution since this way will be teaching tourists how to care for and preserve the environment. This research is intended to serve as examples for other tourist sites with similar problem of environmental pollution other types of pollutants in this way to combat a problem that is not local or regional but it is overall not taking the necessary measures in The issue of reducing and eliminating environmental pollution; As we have already noted, poses a problem and will continue to affect the ecosystem and the biodiversity space where human beings coexist.